2022
DOI: 10.3389/fevo.2022.1033730
|View full text |Cite
|
Sign up to set email alerts
|

Undercover operation: Belowground insect herbivory modifies systemic plant defense and repels aboveground foraging insect herbivores

Abstract: Plants attacked by insects may induce defenses locally in attacked plant tissues and/or systemically in non-attacked tissues, such as aboveground herbivory affecting belowground roots or belowground herbivory modifying aboveground tissues (i.e., cross-compartment systemic defense). Through induced systemic plant defenses, above-and belowground insect herbivores indirectly interact when feeding on a shared host plant. However, determining the systemic effects of herbivory on cross-compartment plant tissues and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 83 publications
4
6
0
Order By: Relevance
“…In this study, we characterised systemic aboveground volatiles of nondamaged and belowground larvae‐damaged plants. We found an increase in aboveground emission of ( E )‐β‐ocimene from belowground larvae‐damaged plants, which mirrored previous findings in a different squash cultivar (Thompson et al, 2022). Similarities in systemic HIPVs across cultivars suggest ( E )‐β‐ocimene may be a conserved signal of herbivory in squash, providing new insights into systemic defence induction and plant signalling in this system.…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…In this study, we characterised systemic aboveground volatiles of nondamaged and belowground larvae‐damaged plants. We found an increase in aboveground emission of ( E )‐β‐ocimene from belowground larvae‐damaged plants, which mirrored previous findings in a different squash cultivar (Thompson et al, 2022). Similarities in systemic HIPVs across cultivars suggest ( E )‐β‐ocimene may be a conserved signal of herbivory in squash, providing new insights into systemic defence induction and plant signalling in this system.…”
Section: Discussionsupporting
confidence: 90%
“…In response to herbivory, plants can redistribute nutrients and shift resources away from insects (Johnson et al, 2009; Orians et al, 2011; Steinbrenner et al, 2011), indicating HIPV‐exposure could possibly preempt nutrient changes that reduce squash bug performance. Notably, our previous research detected similar changes in plant nutrients: belowground larval herbivory increased aboveground protein content and the ratio of protein: carbohydrates, while decreasing aboveground carbohydrates (Thompson et al, 2022). We further demonstrated that squash bugs avoided larvae‐damaged plants, preferring to settle and lay eggs on nondamaged control plants (Thompson et al, 2022).…”
Section: Discussionsupporting
confidence: 54%
See 3 more Smart Citations